Emotional challenges of teaching online during pandemic - Ribeiro, Neuza (2022)
It's no secret that teaching online is becoming more and more popular. The COVID-19 situation is forcing many faculty members to shift online. Besides the convenience and flexibility of this form of teaching, teachers and students are having a harder time connecting on an emotional level. As well as knowledge and cognition, teaching is an emotional activity. Teachers' emotions have received little research, and online instructors’ emotions are even less studied. This research formulated seven themes: student involvement, emotional connection, the benefits and problems of online teaching, the benefits and challenges of in-person teaching, and individual selection of medium. In this chapter, engagement, variety, emotional connection, the Internet as a connection medium unique to itself, spontaneity, emotional contagion, personal suffering, and preference of medium were discussed in detail. As a result of the research, it was concluded that emotional connections might be made online. Instructors just need to employ certain strategies to emotionally connect pupils. For example, teachers can expose themselves by discussing details of their personal stories, by checking in with students regularly and by asking questions, by confirming their personal experiences, and by using Zoom and PowerPoint’s voiceover functionality.